Lessons Learned after Iatrogenic Complete Transection of the Right Common Carotid Artery with Segmental Vessel Loss - Shamir O. Cawich; Wendell Dwarika; Fawwaz Mohammed; Michael J. Ramdass; Vindra Ragoonanan; Megan Augustus; Dave Harnanan; Vijay Naraynsingh; Richard Spence (Case Reports in Vascular Medicine)
Carotid arterial injuries occur in 5-6% of persons with penetrating trauma. Complete transection is rare in civilian practice and is most often due to penetrating injuries. Complete transection as an iatrogenic complication is rare. We present a case where we were required to repair a complete transection of the carotid artery with segmental loss which occurred as an iatrogenic complication during thyroidectomy. We could find no previous reports of this type of iatrogenic complication. The lessons learned during the management of this case were the following: (1) surgeons should call for help early, (2) a multidisciplinary approach ensures that all options are considered, (3) adhere to surgical principles of proximal and distal control, (4) always use atraumatic clamps to control vessels, and (5) flow restoration should be attempted, leaving carotid ligation as the last resort.